ANALISIS POLA TABUHAN BERUAS PADA MUSIK IRINGAN TARI JEPIN TALI BINTANG DI DESA KALIMAS KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Syahbandi, Heri (TACET Jurnal Pendidikan dan Kajian Seni, 2024)
Background of this research is that there are no Beruas musical instruments as accompaniment to Jepin Tali Bintang Dance music, especially in Kalimas Village, Sungai Kakap District, Kubu Raya Regency. This has become an issue and concern of the supporting community for traditional arts because it can experience extinction if it is not maintained and preserved. Through the analysis of Beruas drumming patterns in Jepin Tali Bintang dance accompaniment music, this research aims to describe the variety of drumming patterns in the form of transcripts so that it can be a means for Beruas players and the younger generation who want to learn Beruas instruments. Research method uses descriptive qualitative with a musicological approach. Data collection techniques were observation and interview. The data validity test used source triangulation and extended observation. The results of the study found that there are five types of Beruas beating patterns used in Jepin Tali Bintang Dance accompaniment music, namely extra jepin beating patterns, lapas, tahkto, gencat, and lempas gencat. As for the Beruas beat pattern, there are three Beruas instruments that have rhythmic functions, namely Beruas Induk, Beruas Anak, and Beruas Tingkahan. The characteristics of the Beruas instrument also produce the sound colors dung, tang, and pak. In the future, this research needs to be comprehensively deepened related to the documentation of Beruas drumming patterns and playing techniques so that this study and research becomes complete, especially as a form of preservation of traditional Malay musical instruments.